Characteristic of Postoperative Visual Acuity and Complications of Surgical Procedure on Posterior Polar Cataract Patients at Cicendo Eye Hospital National Eye Center - Rani Pitta; Andrew Knoch; Budiman; Emma Sugiarti (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2021)
Introduction: Posterior polar cataract is a rare form of cataract with incidence from 3 to 5 in 1000. It is bilateral in 65–80% of the cases with no gender predilection. Posterior polar cataract presents a special challenge to the surgeon because of its predisposition to posterior capsular dehiscence and possible nucleus drop during surgery. Purpose: The study aims to evaluate the visual outcome and complication of cataract surgery in patients with posterior polar cataract.Material and Methods: This is an observational study. Data were collected from the medical records within period of January 2016 – December 2018 in National Eye Center Cicendo Eye Hospital and reviewed retrospectively. Subjects in this study are patients with posterior polar cataract who underwent cataract surgery. The outcomes included visual acuity on the fourth week after surgery and complications during cataract surgery. Results: There were 50 eyes of 37 patients included in the study. The mean age was 55.22±13.86 years. Best corrected visual acuity outcomes (BCVA) were 6/6-6/18 in 48 eyes (96%) after surgery. Complications during surgery were found in 7 eyes (14%), which was posterior capsular rupture with vitreous prolapse. Complications during phacoemulsification technique in 6 patients and 1 patient had SICS. Conclusion: Posterior polar cataracts are surgical challenge. In our study, cataract surgery in posterior polar cataract leads to good visual outcome. Appropriate treatment in patients with complications yielding good outcome.